Memo to the new commissioner for energy - Georg Zachmann (Bruegel, 2009)
In this paper Resident Scholar Georg Zachmann analyses the recent developments in European energy policy and looks at the upcoming challenges in this area making a number of recommendations to the newly appointed Energy Commissioner. Zachmann notes that while liberalising energy markets and combating climate change will remain top priorities in the next term of office, securing energy supplies and energy price issues might temporarily lose some appeal due to the crisis-induced energy demand dip. He claims that mitigating climate change, directing investments in network infrastructure and creating a single energy market should be the three interlinked priorities for the Energy Commissioner.
Keywords: 330; EU-Energiepolitik; EU-Staaten